Licensing as a commercialization strategy to improve varietal adoption in Tanzania - Kuhlmann, Katrin; Adron Naggayi Nalinya; Sawe, Irene; Gichuru, Lilian; Ojiewo, Chris O. (International Maize and Wheat Improvement Center, 2024)
Unfortunately, many improved varieties developed and released by African National Agricultural Research Institutions (NARES) remain shelved, never reaching the final intended beneficiaries—the farmers. This brief summarizes key findings from a study done in Tanzania on how the Tanzania Agricultural Research Institution (TARI) could strategically explore licensing to commercialize and improve varietal adoption. The findings show a dire need to develop institutional and industrial capacity for licensing and to revise the TARI legal framework in order to expand the range of varieties that can be licensed. The recommendations contained in this brief were based on consultations with stakeholders and workshop discussions in October and December 2023, led by the New Markets Lab (NML) in collaboration with the International Maize and Wheat Improvement Center (CIMMYT). The results revealed that the NARES have a limited knowledge of licensing and intellectual property rights in the form of Plant Breeders’ Rights (PBR), which is a stringent legal requirement for the protection of varieties prior to licensing in Tanzania that poses a challenge for TARI. The consultations also highlighted institutional gaps in coordinating and overseeing the implementation of licensing agreements and the absence of an institutional intellectual assets policy and a varietal licensing database that are key factors affecting licensing.